ANALYSIS OF FINANCIAL STATEMENT THROUGH RISK-BASED BANK RATING (RBBR) APPROACH TO PREDICT THE BANK HEALTH LEVEL LISTED IN INDONESIAN STOCK EXCHANGE PERIOD 2013-2017 - Fadhila, Indri (Jurnal Manajemen Update, 2019)
ABSTRACTThe purpose of this research was to analyze the financial statement through Risk Base Bank Rating ( RBBR ) on the 30 banking companies listed in Indonesia Stock Exchange (IDX) in the period 2013-2017. The sampling technique used in this study is purposive sampling. The data analysis technique used to test the hypothesis is logistic regression with statistical applied program with SPSS. Based on the result of this study it found that the Non-Performing Loans (NPL) and Good Corporate Governance (GCG) have not significant affect on health level of Banking Company. However, the result of Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Return On Asset (ROA), and Capital Adequacy Ratio (CAR), have significant affect on Health level of Banking Company. Keywords: Non-Performing Loans (NPL), Good Corporate Governance (GCG), Deposit Ratio (LDR), Net Interest Margin (NIM), Return On Asset (ROA), Capital Adequacy Ratio (CAR), health bank level, Logistic Regression